Bibliometric Analysis of Research on the Accreditation Process in Counselor Education - Firdevs Öztürk; Nagihan Oğuz Duran (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
This study aimed to present a bibliometric analysis of the scientific studies on the accreditation process in counseling education in the world. Bibliometric analysis is defined as "a method of analysis that quantitatively examines scientific publications to provide insights into the current status, trends, and development of studies within the literature." The dataset comprised 61 studies published between 1981 and 2024, identified through a search using the keywords “accre*” and “counsel*” in the Web of Science (WoS) database on September 13, 2024. VOSviewer 1.6.20 software was used for the analysis. The studies were analyzed based on publication years, types, countries, languages, journals, institutions, citation counts, and keywords. The findings indicated that although publications on the accreditation process in counselor education began in 1980, the overall number of publications was relatively low, except for the periods between 1990-1994 and 2010-2014, which can be expressed as peaks in terms of the number of publications. The most frequently used keyword was “accreditation,” followed by “CACREP” and “counselor education.” Most studies originated from the United States and were published in English. Among the most cited articles, an article from Turkey ranked third. The journal that published the most articles on this subject was Journal of Counseling and Development. In conclusion, this study provides a comprehensive assessment of quantitative trends in the scientific literature on accreditation processes in counselor education. The findings, which highlight the limited number of publications over a span of more than 40 years, were discussed in relation to potential contributing factors. Additionally, recommendations were offered to enhance accreditation processes and foster research in counselor education, particularly in Turkey.